Improving conditions for transferring family enterprises in Estonia. Pereettevõtte üleandmise võimalustest Eestis - Güldenkoh, Maret (Estonian Discussions on Economic Policy, 2014)
Family enterprise is a business entity that belongs to the family. In Estonia the concept of family business, family entrepreneur, or family enterprise has not been defined in legislation. The concepts of business and enterprise have been defined in several pieces of law with some dissensions in their interpretations, however. Differences in legal definitions become obvious when transferring a business. The aim of the article is to assess the legislative conditions of family enterprises in Estonia. Family enterprises can be transferred either by way of transferring the holding status or by transferring the enterprise. Holding can be transferred in companies; a sole proprietor should transfer the business entity either as a whole or transfer the business entity into a company to have a holding there. Family businesses operating as sole proprietors may incur tax liability by transferring the family enterprise. The paper outlines special features of transferring enterprises, including family enterprises in Estonia. Business transfers have been few and there is no unambiguous practice in this sphere. Transfer of family enterprises is identified with transfer of enterprises; differences arise when family business has been registered as a sole proprietor. The paper provides a brief description of the differences in transferring enterprises, including family enterprises in Estonia. A purpose was to evaluate the legal environment of transferring family enterprises. In Estonia guidelines should be formulated for transferring the business of a self-employed family member and legal regulations should be introduced to avoid ill-intentioned transfer of enterprises.